2020
DOI: 10.7759/cureus.8837
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID-19 due to Shortage of Personal Protective Equipment

Abstract: The supply of personal protective equipment (PPE) is inadequate throughout the United States and the world. This is especially true of N95 respirators. The cost of PPE is high. There are numerous cases of providers working with inadequate PPE and being disciplined on complaining. In the United States, thousands of providers have contracted COVID-19, in part due to inadequate PPE. Extended use and reuse of N95 respirators has been permitted by the Centers for Disease Control and Prevention (CDC). The N95 respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
0
31
1
Order By: Relevance
“…32 Healthcare workers at high risk are safe when appropriate PPEs are used while caring for COVID-19 patients; however, a shortage of PPEs could put them at substantial risk of becoming infected with SARS-COV-2. 33 The translation of high risk of COVID-19 virus infection into a positive COVID-19 test has been reported in the US. 28 For HCWs at high risk of COVID-19 virus infection, WHO recommends suspension of all forms of healthcare interactions with patients, being/getting tested for COVID-19 and quarantined for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…32 Healthcare workers at high risk are safe when appropriate PPEs are used while caring for COVID-19 patients; however, a shortage of PPEs could put them at substantial risk of becoming infected with SARS-COV-2. 33 The translation of high risk of COVID-19 virus infection into a positive COVID-19 test has been reported in the US. 28 For HCWs at high risk of COVID-19 virus infection, WHO recommends suspension of all forms of healthcare interactions with patients, being/getting tested for COVID-19 and quarantined for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Supply shortages of PPE have been previously reported during the pandemic as well as the role they could play in nosocomial infection. ( 53 , 54 , 55 ) Therefore, while heightened IPC protocols may assist in further control of HAIs, an ongoing challenge will be balancing these measures with other immediate clinical demands.…”
Section: Covid-19 and Infection Prevention And Controlmentioning
confidence: 99%
“…A study from China reported which results in improved radiologic findings, enhanced viral clearance, and reduced disease progression by treating successfully with CQ on 100 COVID-19 cases. 31 When treatment given to 6 patients, then it is observed that as compared to HCQ monotherapy (8/14, 57%) the combination of azithromycin with HCQ (6/6, 100%) results in numerically superior viral clearance. 32 …”
Section: Hydroxychloroquine (Hcq) Andchloroquine (Cq)mentioning
confidence: 99%